Multimodality and disciplinary learning: the case of purposeful transformation in the sciences - Kapodistrias, Anastasios; Airey, John (Frontiers in Communication, 2025)
IntroductionIn this paper we discuss disciplinary learning and the roles that different modalities can play in the process. We first describe the extant research in the field of social semiotics with an emphasis on the functions of affordance and transduction in university science, before presenting the comparatively sparse research on transformation. Our goal is to identify whether the process of transformation, besides its previously described procedural functions, can have important meaning making functions as well.MethodsTaking the discipline of cosmology as our point of reference, our data consist of four different forms of the mathematical rearrangement of the Friedmann equation, as observed in university lectures. We analyzed these forms for their meaning making functions using abductive reasoning and the framework of symbolic forms.ResultsWe identify an important, hitherto undescribed type of meaning-making —purposeful transformation. We describe its key characteristics (narrowing down meaning potential, foreground-background movement and purposeful direction) and we provide a first definition.DiscussionFirst, we discuss the implications of our findings on social semiotics theory, focusing on the notions of disciplinary and pedagogical affordance and the possibility of identifying purposeful transformations in other semiotic systems. Finally, we demonstrate its importance in the teaching and learning of natural sciences.